Prototype Android Based Payroll Monitoring Application at PT. Anugrah Distributor Indonesia - Nur Azizah; Sri Rahayu; Bekti Undari (Universitas Raharja, 2020)
A Salary is a form of wages or rewards from rights granted by companies to employees. Usually, salaries are given to workers also differ according to position and class level. At PT Anugrah Distributor Indonesia is one of the companies engaged in retail sales. The amount of wages varies as well as determining commissions for each sales process from each unit. Become a complexity factor in determining the amount and salary for employees. In the process of recording and calculating salaries so far using Ms. Excel. Where accountants (finance) as data processors have a central role in processing them experiencing delays in displaying data. The results of the management process and salary reports are in the form of paper and files (softcopy). Delays in displaying data have an impact on the salary that must be reported by the leadership. From these problems, problem-solving is obtained by making an android-based payroll monitoring application prototype, can display salary data and make it easier for leaders to see the salary that has been reported anytime and anywhere. This research was made using observation methods, interview methods, SWOT analysts and literature studies. Using UML as a modeling design.